Magnetic nanomaterials catalyzed synthesis of tetrazoles. Issue 17 (1st September 2020) - Aqeel Ashraf, Muhammad; Liu, Zhenling; Yang, Yafeng; Li, Cheng; Zhang, Dangquan
Abstract: Tetrazoles are valuable molecules in pharmaceutical and agriculture chemistry, because they are excited in many drugs, natural products and biologically active molecules. During the last decade, magnetic nanomaterials have appeared as highly efficient catalysts in chemical science in general organic chemistry, because of their simple preparation, modification, and large surface area ratio. In this paper, we provide an overview of the utilization of magnetic nanomaterials as attractive and efficient catalytic systems in synthesis of biologically active tetrazoles. Graphical Abstract: